ANTI-ULCER ACTIVITY OF AFRICAN LEAVES (VERNONIA AMYGDALINA DEL.) ETHANOL EXTRACT ON MALE RAT - Wahyudi; Suwarso, Edy; Nainggolan, Marline (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objectives: This study aims to evaluate the anti-ulcer activity of African leaves (Vernonia amygdalina Del.) ethanol extract on male rat. Methods: African leaf powder was extracted used ethanol 96% by percolation, then made into a suspension preparation used 0.5% Na-CMC with 3 dose variations (100, 200 and 400 mg/kg). Further tested its effectiveness in healing peptic ulcer in gastric-induced rats using acetosal dose 800 mg/kg with oral administration every day until surgery at 3, 8, and 14. Observations include macroscopic (number and index of ulcer) and microscopic (histopathological test). Results: A significant healing of ulcer was observed. The extract 100, 200, and 400 mg/kg group showed significant (p<0.05) reduction in number and index of ulcer as compared to the negative control. The most effective dose is 200 mg/kg because it has the greatest ability to reduce the number and index of ulcers and has the fastest recovery day. Conclusion: Results of this study indicated that African leaves (V. amygdalina Del.) ethanol extract has potential anti-ulcer activity.